2018
DOI: 10.1080/09638288.2018.1452053
|View full text |Cite
|
Sign up to set email alerts
|

Translation, cross-cultural adaptation, reliability, and validity of the Identification of Functional Ankle Instability questionnaire in Persian speaking participants with a history of ankle sprain

Abstract: The Persian version of IdFAI is a reliable and valid tool to identify patients with functional ankle instability which have a history of ankle sprain. Its original three-factor structure was replicated in this study. Implications for Rehabilitation The Persian version of the Identification of Functional Ankle Instability (IdFAI) questionnaire is a reliable and valid instrument in order to identify Iranian patients with functional ankle instability in both clinical practice and research. The Persian IdFAI quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
3
17
3
Order By: Relevance
“…Therefore, not all the higher Cronbach's α values suggested a better scale [32]. The three subscales of the SC-IdFAI questionnaire also had an acceptable or good internal constancy (Cronbach's α = 0.725-0.882), which were generally in agreement with other previous studies [11,14,19]. The findings also showed that omitting any of the questions would not evidently increase the Cronbach's α value of the SC-IdFAI questionnaire (0.880-0.904).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Therefore, not all the higher Cronbach's α values suggested a better scale [32]. The three subscales of the SC-IdFAI questionnaire also had an acceptable or good internal constancy (Cronbach's α = 0.725-0.882), which were generally in agreement with other previous studies [11,14,19]. The findings also showed that omitting any of the questions would not evidently increase the Cronbach's α value of the SC-IdFAI questionnaire (0.880-0.904).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the mean score of the SC-IdFAI questionnaire was slightly higher than that of the other versions (14.3-20.38) [11,19], suggesting that the severity of the CAI was relatively higher in the patients. In addition, the ceiling effect of SC-IdFAI was 1.52%, but not 0 as shown in other versions, suggesting that very few patients obtained a full score in the scale, but the percentage of the patients was far lower than 15%.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations